EXTRATHYROIDAL INFLUENCE OF HASHIMOTO’S THYROIDITIS – A LITERATURE REVIEW - Jasińska, Lilianna; Niespodziewański, Michał; Szczygielska, Patrycja; Hejna, Sylwia; Teterycz, Weronika; Jaworek, Łukasz; Goździejewska, Weronika; Smutkiewicz, Weronika; Roman, Magdalena; Lipiarz, Martyna (International Journal of Innovative Technologies in Social Science, 2026)
Hashimoto’s thyroiditis (HT) is a chronic lymphocytic inflammation of thyroid gland. The incidence is estimated to be 5% in general population and is higher in women. Primary role in pathogenesis is given to two types of antibodies – anti-peroxidase (anti-TPO) antibodies and anti-thyroglobulin (anti-TG) antibodies that lead to chronic lymphocyte mediated inflammation and thyroid follicular cell destruction. Clinically it usually leads to hypothyroidism and its symptoms like weight gain, cold intolerance, bradycardia and fatigue. As chronic inflammation HT leads to elevated levels of inflammatory factors like Tumor Necrosis Factor α (TNF-α), Interferon-γ (IFN- γ) and high sensitivity C-reactive protein (hs-CRP). Levels of anti-TPO and anti-TG were positively correlated with levels of TNF-α and IFN-γ and severity of symptoms, while they were negatively correlated with general health and vitality score. The overall cancer risk in patients is increased, but HT is negatively associated with primary tumor size of 4 cm or greater, extranodal extension and distant metastasis in Papillary thyroid carcinoma. Hashimoto’s thyroiditis may also have impact on the course of migraine by more migraine days monthly and higher risk of chronic migraine. Level of anti-TPO antibodies is a significant independent risk factor of depressive disorder, while negativity of anti-TG was correlated with lower anxiety levels. That finding suggests that autoantibodies are more important than thyroid hormone levels in pathogenesis of psychiatric disorders. Patients with HT also report lower health-related quality of life.